14. PENGARUH LAMA PERENDAMAN LARVA DALAM HORMON METIL TESTOSTERON ALAMI TERHADAP PENJANTANAN IKAN LELE DUMBO (Clarias gariepinus) The Effect of Soaking Time of African Catfish Larvae (Clarias gariepinus) in Natural Methyl Testosterone Hormone on Masculinization - Rosmaidar R (Universitas Syiah Kuala, 2016)
The purpose of this study was to determine the effect of immersion time on African catfish (Clarias gariepinus) larvae in natural methyl testosterone hormone on masculinization. This study was conducted in Center of Fish Culture Lamnyong, Banda Aceh. Experimental animals used in this study were 270 African catfish larvae aged 10 days. The study was designed using completely randomized design (CRD) with 3 treatments and 3 replications. African catfish larvae aged 10 days in group P1, P2, and P3 were immersed in natural methyl testosterone hormone for 10 hours, 20 hours, and 30 hours, respectively. Observations were carried out until fish reach 50 days old. Data were analyzed by analysis of variance (Anova) followed by least significant difference test (LSD). Percentage of male catfish observed in P1, P2, and P3 were 64.24 %, 93.11%, dan 59.94% respectively. As a conclusion, immersion with natural methyl testosterone hormone can change the sex of catfish to be male. ____________________________________________________________________________________________________________________ Key words: african catfish, methyl testosterone natural, masculinization